(untitled) (Bangladesh Journal of Microbiology, 2018)
Microbial Cellulases have an escalating demand in many industries and constitute a major group of the industrial enzymes. It has attracted the attention of many researchers because of its tremendous industrial applications including textile industry, pulp, and paper industry, laundry and detergent industry, food and animal feed industry. The present study pursues to unfold a novel cellulase that can overcome existing challenges in biorefineries as well as to reduce biofuel production cost. Therefore, soil from a dairy farm was screened for potent cellulase producers on carboxymethylcellulose agar. Out of 68 isolates, 31 expressed cellulase activity. The best isolate so far had an extracellular crude enzyme activity of 0.167 U/ml and specific activity of 0.333 U/mg. The cell morphology, cultural characteristics, and biochemical tests presumptively identified it to belong to the genus Bacillus. Molecular analysis using 16S rRNA gene of the isolate indicated it to be Bacillus subtilis. The optimum pH and temperature for the activity of the crude enzyme were determined to be 5 and 65°C respectively. Bangladesh J Microbiol, Volume 33, Number 1-2, June-Dec 2016, pp 17-22